Enhancing the Supply Chain Management in Construction using Artificial Intelligence - Vraj K.Shah,Mahesh B. Sonawane (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A new wave of digitization is reshaping the construction industry, but it also brings a wealth of new prospects. Building materials manufacturing, planning, design, and construction are all in a supply chain projected to be boosted by artificial intelligence. Along with this, facility management is also expected to benefit from this technology. Choosing the optimal project management solution, particularly for major building projects, is sometimes complicated and fraught with uncertainty. As per the original references, the success and efficiency of project management rely on using three pillars called “Management involvement,”“create and streaming systems,” and “using the tools.”Tools and procedures are directly in the knowledge areas of executives andengineers.On the other hand, the other two pillars rely on the outputs of the tools and procedures indirectly. As a result, tools and methods play a critical part in project management’s effective implementation. However, artificial intelligence includes collectingdata, induction, and experiment analysis to comprehend human intelligence modeling and non-numerical methods to solve complicated issues. Hence it can be used as a tool in four major fields: Integration Management, Project Procurement Management, Project Risk Management, and Project Communications Management;they can be used in numerous applications.